2023
DOI: 10.1001/jamanetworkopen.2023.20513
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index With Outcomes Among Patients With Head and Neck Cancer Treated With Chemoradiotherapy

Abstract: ImportanceCombined modality therapy, such as chemoradiotherapy, often results in significant morbidity among patients with head and neck cancer. Although the role of body mass index (BMI) varies based on cancer subtypes, its association with treatment response, tumor recurrence, and survival outcomes among patients with head and neck cancer remains unclear.ObjectiveTo evaluate the role of BMI in treatment response, tumor recurrence, and survival outcomes among patients with head and neck cancer undergoing chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…Similar to what was reported by several studies [12,[15][16][17][18], our study found that critical weight loss was more pronounced and independently associated with our study population who had a high pretreatment BMI. The majority of our study population had a higher pretreatment BMI: overweight (28%) and obese (26%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to what was reported by several studies [12,[15][16][17][18], our study found that critical weight loss was more pronounced and independently associated with our study population who had a high pretreatment BMI. The majority of our study population had a higher pretreatment BMI: overweight (28%) and obese (26%).…”
Section: Discussionsupporting
confidence: 92%
“…This finding contrasts with those of two studies that found no significant relationship between pretreatment BMI and critical weight loss among cancer patients with several types including HNC undergoing radiotherapy [6,19]. Furthermore, in recent research conducted by Ma et al [15], they observed that HNC patients with a high BMI (overweight or obese) experienced significant weight loss. However, these patients were found to have more positive outcomes, such as improved treatment response, greater overall survival, and increased progression-free survival.…”
Section: Discussioncontrasting
confidence: 66%
“…Patients with OCSCC may exhibit lower BMI values than do individuals in the general population owing to the effects of the cancer and cancer-associated dysphagia; therefore, the mGNRI provides additional insight into patients’ condition by accounting for the patients’ ideal weight, thereby offering a more objective evaluation of the patients’ weight. A previous study observed that being underweight at head and neck cancer (HNC) diagnosis was an independent risk factor for unfavorable prognosis 35 ; conversely, overweight was associated with the likelihood of complete response after CRT 36 . These observations could be linked to cancer-related chronic wasting, oxidative stress, and the high protein metabolism induced by cancer cachexia 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of regions outside the head and neck (renal cell carcinoma, metastatic melanoma, and several others) have demonstrated that obesity is associated with improved oncologic survival in patients with ICI treatment. A retrospective, single-institution cohort study of 445 patients with head and neck cancer of various types and treated with chemoradiotherapy found that pretreatment overweight BMI, but not obesity BMI, was an independent factor associated with improved OS and progression-free survival (PFS) . Zhang et al conducted a retrospective review of 49 patients at a single institution in China who received anti–PD-1 therapy (pembrolizumab) for recurrent or metastatic HNSCC.…”
Section: Discussionmentioning
confidence: 99%